Retrospective Analysis of Pneumonic Tularemia in Operation Whitecoat Human Subjects: Disease Progression and Tetracycline Efficacy - Williams, Mark S.; Baker, Marianne R.; Guina, Tina; Hewitt, Judith A.; Lanning, Lynda; Hill, Heather; May, Jeanine M.; Fogtman, Beverly; Pittman, Phillip R. (Frontiers in Medicine, 2019)
Francisella tularensis is a highly infectious Gram-negative bacterium that is the etiologic agent of tularemia in animals and humans. The incidence of tularemia is very low with a lack of comprehensive data that describe disease in humans due to difficulty in understanding time and routes of exposure. Under the title Operation Whitecoat, researchers at Ft. Detrick, MD conducted 40 clinical studies of tularemia from 1958-1968. In these studies, one of the objectives was to evaluate candidate countermeasures for treatment or prophylaxis of disease after exposure to Francisella tularensis strain Schu S4 by inhalation. These studies were reviewed retrospectively to delineate the early signs and symptoms or “natural history” of pneumonic tularemia and examine the efficacy of tetracycline in controlled human clinical studies. Using vital signs, onset of fever was objectively defined and calculated for each subject, while Adverse Events reported after exposure were also used to define the timing of disease onset and symptoms of early disease. There was a dose response relationship between time to fever onset and exposed dose at 200 cfu (172.8 hr), 700 cfu (163.2 hr), 2,500 cfu (105.3 hr) and 25,000 cfu (75.5 hr). Onset of fever was typically the earliest sign of disease at all doses but was often accompanied by symptoms such as headache, myalgia, chest pain and nausea, irrespective of dose except at 200 cfu where only 50% of subjects exhibited fever onset or symptoms. Examining the efficacy of different treatment regimens of tetracycline, ineffective treatments were indicated by relapse of disease (fever and Adverse Events) after cessation of antibiotic treatment. Stratification of the data suggested that treatment for less than 14 days or doses less than 2g/day was associated with increased percentage of subjects with relapse of disease symptoms. Although these types of human challenge studies would not be ethically possible now, the climate post-World War II supported human testing under rigorous conditions with informed consent. Thus, going back and analyzing these unique clinical human challenge studies has helped describe the course of infection and disease induced by a biothreat pathogen and possible countermeasures for treatment under controlled conditions.